2003
DOI: 10.1051/vetres:2002065
|View full text |Cite
|
Sign up to set email alerts
|

How the surveillance system may bias the results of analytical epidemiological studies on BSE: prevalence among dairy versus beef suckler cattle breeds in France

Abstract: -Until recently, epidemiological studies on Bovine Spongiform Encephalopathy (BSE) were based on Mandatory Reporting Systems (MRS) of clinically suspect bovines only, but rapid diagnostic tests were validated in 1999 and are used for targeted surveillance in Switzerland, France and other countries, as a complementary and secondary tool. Data on 30491 cattle issued from a French pilot program targeted at cattle having died on the farm, subjected to euthanasia or sent for emergency slaughter, did not show any si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…So, in order to define a study sample in which cases and controls have been submitted to a global comparable level of risk, they were matched on their birth cohort. The production type of cattle, dairy or beef, was also considered as a potential confounding factor [13,23]. Since the farmer practices concerning the cattle feeding were related 512 N. Jarrige et al to the production type, it was decided not to pair cases and controls on this factor to avoid a possible overmatching bias but to consider it as a potential confounder in the model.…”
Section: Discussionmentioning
confidence: 99%
“…So, in order to define a study sample in which cases and controls have been submitted to a global comparable level of risk, they were matched on their birth cohort. The production type of cattle, dairy or beef, was also considered as a potential confounding factor [13,23]. Since the farmer practices concerning the cattle feeding were related 512 N. Jarrige et al to the production type, it was decided not to pair cases and controls on this factor to avoid a possible overmatching bias but to consider it as a potential confounder in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Since then different complementary surveillance programmes have been organised [1], based on rapid tests [22]; they showed that the clinical surveillance alone misses a great proportion of diseased animals [15,20]. This is the reason why a comprehensive system is now implemented to detect BSE cases, including clinical surveillance, test on dead cattle (fallen stock), and systematic screening at the abattoir; the tests are carried out on cattle aged two years and more (over 30 months old before July 2001 at the abattoir).…”
Section: Introductionmentioning
confidence: 99%
“…It could be demonstrated through retrospective investigations that more than half of the cases found by active surveillance had displayed clinical signs before death, either characteristic for BSE or at least sufficiently suggestive [18,29]. Also, comparing cases found by active and passive surveillance during the same period of time (passive surveillance takes place before death/slaughter) showed biases in the type of animals detected by passive surveillance, the ability to detect beef cow cases being far less efficient than detection of dairy cases [33].…”
Section: Active Surveillancementioning
confidence: 99%
“…For example, in both the UK and France it has been identified that dairy cows have a risk of BSE approximately three times higher than that of beef cows, once confounding factors such as age at culling or region of origin have been accounted for [33,45,68]. This is simply explained by a higher use of compound feed in dairy farms.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation